Literature Review: Kebijakan Publik terhadap Pengadaan Barang Modal Strategis Lembaga Pemerintah Indonesia - Ni Nyoman Kartika Yanti (Universitas Warmadewa, 2023)
The faster Indonesia's and the world's economies grow, the greater the benefits to the government and society. Rapid growth, on the other hand, can lead to an increase in fraud. The implementation of electronic procurement is one of the government's policy reforms aimed at increasing the procurement of government goods and services (e-procurement). The goal of this research is to examine public policy regarding the acquisition of strategic capital goods for Indonesian government institutions. The research design for this qualitative study is a literature review. Agency theory was used to analyze this study. The findings demonstrate the importance of focusing on public policies with good governance by leveraging the potential of simple e-procurement to reduce fraud, which can have an impact on a country's level of corruption.